The Effectiveness of Lemongrass, Garlic, and Tree Marigold as Botanical Insecticides in Controlling of Cocoa Mirid,Helopeltis antonii - Endang Sulistyowati; Muhammad Ghorir; Suryo Wardani; Setyo Purwoko (Indonesian Coffee and Cocoa Research Institute, 2014)
Control of cocoa mirid, Helopeltis antoniiso far uses chemicalinsecticides as the main alternative. Therefore, it is necessary to find out the environment friendly control techniques. Lemongrass, garlic, and tree marigold have been known as an efectiveness botanical insecticides for horticulture. A research with aim to study the effectiveness of lemongrass (Cymbopogon nardus), garlic (Allium sativum) and tree marigold (Tithonia diversifolia)for controlling H. antoniihave been carried out in cocoa plantation at Kaliwining experimental garden of Indonesian Coffee and Cocoa Research Institute. The research was arranged in split plot design in three replication, with the main plot infestation time of H. antoniiand sub-plot kind of botanical insecticides. Concentration of botanical insecticides used in this study was 5% and applied on 12 cm cocoa pod in length by using knapsack sprayer. Infestation of H. antonii nymphes were conducted before and after insecticide applications. Observation was conducted on the mortality and the lesion of H. antonii. The results of orthogonal contrast test on feeding activity based on the number of lesion and percentage of mortality of H. antoniishowed that there were significantly different between insecticide treatment and control, between chemical insecticide and botanical insecticides, but there was no significant different on kind of botanical insecticides. The lowest number of lesion due to H. antonii was shown by chemical insecticide with an average 34.0, followed by garlic and lemongrass botanical insecticide with number of lesion were 51.2 and 64.7 respectively, whereas the number of lesion in the control reached 84.2. The highest percentage mortality of H. antoniiwas shown by chemical insecticide with active ingredient teta-cypermethrin at 84.3%, followed by garlic, lemon grass and tree marigold botanical insecticide were 65.8%; 65.0%; and 63.8% respectively and significantly different with control by 8,3%. Based on no significantly different on the effect of time investation of H. antoniion their feeding activity and mortality, it can be concluded that the three botanical insecticides tested have a mode of action both as a repellent and contact poison. Key words: cocoa, Helopeltis antonii, botanical insecticide, lemongrass, garlic, marigold, teta-cypermethrin